Metodología para la evaluación alimentaria y nutricional desde una perspectiva de equidad (2015)
ABSTRACT: In Latin America, the new social policies to fight on poverty have food and nutrition programs as the spotlight, whose social impact is assessed in most cases based on their biological outcomes or administrative criteria such as compliance with selection beneficiaries. Our proposed model to evaluate nutritional programs combines qualitative and quantitative methods and incorporates the evaluation of the structure, processes and outcomes in the following dimensions: food and nutrition security, right to food, citizenship, territorial planning, empowerment of women and program management. The evaluation results include the perception of different actors such as recipients of programs and those involved in its implementation.